Severe headache in primary Sjögren’s syndrome treated with intrathecal rituximab - Anne Bolette Tjensvoll; Maria Boge Lauvsnes; Katrine Brekke Norheim; Roald Omdal (Clinical Case Reports, 2019)
Key Clinical Message A severe and persistent migrainous headache in a patient with primary Sjøgren's syndrome unresponsive to treatment with immunosuppressive drugs, triptans, opioids, and NSAIDs, responded successfully to intrathecal B‐cell depletion with rituximab. We hypothesize that brain‐resident autoreactive B cells were involved in headache pathogenesis and were eliminated by this procedure.